Molecular insights into the membrane affinities of model hydrophobes - Li, Jianguo (2019)
Membrane-active antibiotics are of great interest in fighting bacterial resistance. α-Mangostin is a membrane-active molecule, but there are no details of its mechanism of action at the atomistic level. We have employed free-energy simulations and microsecond-long conventional molecular dynamics simulations to study the mode of interaction of α-mangostin with a model bacterial membrane and compare it with the mechanisms of three hydrophobic molecules (ciprofloxacin, xanthone, and tetracycline). We find that α-mangostin is thermodynamically more favored to insert into the membrane compared to the other three molecules. Apart from tetracycline, which is largely hydrophilic, the other three molecules aggregate in water; however, only α-mangostin can penetrate into the lipid tail region of the membrane. When it reaches a high concentration in the lipid tail region, α-mangostin can form tubular clusters that span the two head group regions of the membrane, resulting in a large number of water translocations along the transmembrane aggregates. Structure–activity relationship analysis revealed two structural properties that characterize α-mangostin, namely, the two isoprenyl groups and the polar groups present in the aromatic rings, which result in “disruptive amphiphilicity” and hence its excellent membrane activity.